2020
DOI: 10.1016/j.jcsr.2020.106278
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of collar plate reinforced SHS T-joints: Effect of geometrical parameters and chord stress ratio

Abstract: The collar plate (CP) is applicable for the reinforcement of both new designed and in-service joints, yet the design approach for the reinforcement requires further investigation. The current paper investigates the effect of various geometrical parameters as well as chord stress ratios on the compressive capacity of the collar plate reinforced (CPR) square hollow section (SHS) T-joints. The finite element (FE) models of the CPR SHS T-joints are built and validated using experimental data. Extensive parametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the effort to improve the strength of the RHS joints, many strengthening measures have received attention. For example, collar plate strengthening for the T-joints was studied by Chang et al [21], sidewall plate strengthening for the T-joints was studied by Gomes et al [22], and the seismic behavior of a prefabricated steel-braced frame structure with hinged joints was studied by Jia et al [23]. It was found that these strengthening measures could effectively increase the strength of the RHS joints.…”
Section: Introductionmentioning
confidence: 99%
“…In the effort to improve the strength of the RHS joints, many strengthening measures have received attention. For example, collar plate strengthening for the T-joints was studied by Chang et al [21], sidewall plate strengthening for the T-joints was studied by Gomes et al [22], and the seismic behavior of a prefabricated steel-braced frame structure with hinged joints was studied by Jia et al [23]. It was found that these strengthening measures could effectively increase the strength of the RHS joints.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other recent studies (Kim and Lee, 2020; Lima et al, 2018a; Nizer et al, 2016) have shown that, depending on the intensity of tension stresses in a chord, an increase in joint resistance could occur, what was never found in compression cases. For cases with compression stresses, the brace-to-chord ratio was identified as a critical parameter that influenced the joint strength of T-joints with reinforcements (Chang et al, 2020). Therefore, for the consideration of the effect of the stresses from axial forces and bending moments acting in the chord and affecting the joint resistance, adequate chord stress functions are fundamental for the proper joint design.…”
Section: Introductionmentioning
confidence: 99%